Social and cultural factors of transformation of network forms of business in modern Russia (Путеводитель предпринимателя)
Essential increase of attention to problems of development of enterprise networks in modern Russia is based on considerable advantages of this model of enterprise interaction. Nevertheless, the major part of the researches devoted to challenges of a turning to the network of economy, relies on studying of problems of globalization of economy and introduction of the new technologies facilitating interaction of the enterprises, laying aside sociocultural factors of translation of network forms of business in domestic economy.